A Motion-Compensated Overcomplete Temporal Decomposition for Multiple Description Scalable Video Coding. (19th February 2007) - Tillier, Christophe; Petrişor, Teodora; Pesquet-Popescu, Béatrice
Abstract : We present a new multiple-description coding (MDC) method for scalable video, designed for transmission over error-prone networks. We employ a redundant motion-compensated scheme derived from the Haar multiresolution analysis, in order to build temporally correlated descriptions in at + 2 D video coder. Our scheme presents a redundancy which decreases with the resolution level. This is achieved by additionally subsampling some of the wavelet temporal subbanbds. We present an equivalent four-band lifting implementation leading to simple central and side decoders as well as a packet-based reconstruction strategy in order to cope with random packet losses.